A Comparative Study between Rosuvastatin and NanoRosuvastatin Effects on Liver in Mice that Consuming Diets Rich in Vegetable Oil - Zahraa Saad Hussain; Jasem Hanoon Hashim Al-Awadi (Indian Journal of Forensic Medicine & Toxicology, 2021)
The study was designed to evaluate the histological changes occurring in mice liver subjected to a highfat diet for 4 months, and to assess the effectiveness of Rosuvastatin drug in its two forms (free and nano) in alleviating these changes. Consumption of a high-fat diet (vegetable oil) resulted in mild to severe lymphocytes infiltration, sever lipid accumulation as macro and microvesicularsteatosis, necrosis, pyknotic nuclei. The histology of liver sectionsobtained from mice treated with rosuvastatin showed lower severity in comparing with positive control mice. Histological changes include infiltrated lymphocytes, pyknotic nuclei, apoptotic cells. Furthermore,Liver sections from the Rosuvastatin treatment group showed ameliorated steatosis when comparedto a high-fat diet treated group. Liver sectionsof thenanoRosuvastatintreated group showed much more improvement comparedtoRosuvastatin treated group.